Metastatic Seminoma with Positive Staining of Cytokeratin and MOC31: A Diagnostic Pitfall. (30th June 2021) - Fan, Jiaming; Yuan, Ren; Stefanelli, David; Wang, Gang
Abstract : Retroperitoneal metastasis of seminoma often occurs in the higher stage through lymph nodes. Generally, seminoma expresses specific germ cell markers while being negative for carcinoma markers. We present a unique case of cytokeratin positive seminoma initially presented as retroperitoneal metastasis. The diagnosis was made based on the histological features and immunohistochemical stains. Testicular ultrasound confirmed the primary tumor in the patient's left testicle. Pathologists should always be aware of germ cell tumors when encountering a metastasis of an unknown primary.